Practical management of chronic fatigue syndrome or myalgic encephalomyelitis in childhood. Issue 10 (28th June 2017) - Brigden, Amberly; Loades, Maria; Abbott, Anna; Bond-Kendall, Joanne; Crawley, Esther
Abstract : Paediatric chronic fatigue syndrome or myalgic encephalomyelitis affects at least 1% of secondary school children in the UK and is very disabling. Treatment is effective but few children get a diagnosis or access treatment. This paper summarises what we currently know about diagnosing and treating this important illness in childhood.